2019
DOI: 10.4995/eurocall.2019.11024
|View full text |Cite
|
Sign up to set email alerts
|

A review of MALL: from categories to implementation. The case of Apple’s iPad

Abstract: <p>The use of mobile devices inside and outside formal settings is often associated to innovative practices in the design of language learning activities. This often implies the reconceptualization of language learning tasks and of the role of the teacher in the mobile classroom. In order to investigate current research and practices in secondary and higher education a review of recent studies in the field of MALL has been undertaken with the main aim of identifying main trends, implementation practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Mobile learning here refers to learning that takes place through the medium of mobile devices (Althunibat, 2015). Mobile applications and platforms have increasingly supported language learning (Godwin-Jones, 2011;Heil et al, 2016;Morgana, 2019;Stanley, 2013;Tommerdahl et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile learning here refers to learning that takes place through the medium of mobile devices (Althunibat, 2015). Mobile applications and platforms have increasingly supported language learning (Godwin-Jones, 2011;Heil et al, 2016;Morgana, 2019;Stanley, 2013;Tommerdahl et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study on a review of MALL revealed that many studies are more descriptive than innovative and advocate the implementation of larger and long-term research studies on how mobile devices, and the iPad in particular, are impacting language teaching and learning. (Morgana, 2019). Other papers have highlighted the focus on the impact of MALL on fostering the EFL instruction (Imtiaz, Norrihan, Aslam, Waqar, 2016), the role of smartphones in helping students enhance their social and cultural capital (Retorta, and Cristovão, 2017), utilization of Instagram vlog contributed to EFL learners' speaking skill on enhancing fluency, acquiring vocabulary items, and boosting confidence and motivation (Wulandari, 2019), and the effect of MALL in improving students' motivation (Teeter, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Language learning apps and platforms have become widely available through mobile technologies, and many have freely accessible resources that cater in particular for ab initio learners. Mobile assisted language learning (MALL) for tutorial apps (Morgana, 2019: 2), such as Duolingo or Memrise, are just two examples of digital tools that allow ab initio learners to engage in structured language learning activities in a flexible yet structured and directed way. In order to contribute to the development of autonomy, the suggestion is to encourage learners to compare their experience with different apps to better understand the affordances and limitations of these platforms.…”
Section: Discussion and Reflection Of Outcomes And Experiencesmentioning
confidence: 99%